PENGEMBANGAN E- MODUL INTERAKTIF BERBASIS PROBLEM BASED LEARNING DENGAN MENGOPTIMALKAN ASPEK 4C UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI LISTRIK DINAMIS - Umi Laila Ramadhan; Isnanik Juni Fitriyah; Umi Laila Ramadhan (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
The development of 21st century education requires students not only to understand material concepts but also to have skills. Therefore, it is necessary to have innovative and interactive learning media that can support the student learning process. This study aims to develop an interactive e-module based on problem-based learning by optimizing the 4C aspect to increase students' understanding of dynamic electrical materials. This research is a Research and Development (RnD) study. The method used in this study is ADDIE which consists of the analysis, design, development, implementation, and evaluation stages. The subjects of this research were 31 grade IX students of SMP Negeri 1 Turen. The data collection techniques used are observation, questionnaire analysis of student and teacher needs, questionnaire validation of concept correctness, product feasibility test questionnaire, media feasibility test questionnaire, truth questionnaire about pre-test post-test, questionnaire on teacher and student practicality and assessment instruments in the form of pretest and post-test. A media eligibility validation score of 86.80% was obtained with a very valid category. The material eligibility validation score was 90.62% with a very valid category. The average result of the teacher and student practicality test was 94.79% with a very valid category. The e-module effectiveness test obtained an N-gain score percentage of 71,92% which states that problem-based learning-based interactive e-modules by optimizing the 4C aspect are effective for improving students' understanding of dynamic electrical materials.